2019
DOI: 10.1002/hpm.2778
|View full text |Cite
|
Sign up to set email alerts
|

Do quality improvements in assisted reproduction technology increase patient numbers in a managed competition setting?

Abstract: Summary In a system of managed competition, selective contracting and patient choice reward providers for quality improvements through increases in patient numbers and revenue. We research whether these mechanisms function as envisioned by investigating the relationship between quality improvements and patient numbers in assisted reproduction technology in the Netherlands. Success rate improvements primarily reduce volume as fewer secondary treatments are necessary, but this can be compensated by attracting ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Studies on the relation between quality and selective contracting in the managed competition sector in the Netherlands are limited, and show mixed results. 56 - 58 Studies on price competition in the Dutch hospital-sector also show limited responsiveness of insurers to price differences. 14 , 15 , 59 One study found an increase in total costs of inpatient DRGs after the introduction of market-based price competition, but a decrease in total costs of outpatient DRGs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the relation between quality and selective contracting in the managed competition sector in the Netherlands are limited, and show mixed results. 56 - 58 Studies on price competition in the Dutch hospital-sector also show limited responsiveness of insurers to price differences. 14 , 15 , 59 One study found an increase in total costs of inpatient DRGs after the introduction of market-based price competition, but a decrease in total costs of outpatient DRGs.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 47 - 49 One potential explanation for these conflicting findings is that growth in the number of new patients may not correlate with growth in hospital expenditures, for example when prices or treatment intensity decline correspondingly. 50 Furthermore, it remains unclear whether active purchasing or patient choice drives these results. 43 , 50 Paradoxically, we found extensive differences in selective contracting between providers and over time, without any distinguishable effect on provider budgets.…”
Section: Discussionmentioning
confidence: 99%
“… 50 Furthermore, it remains unclear whether active purchasing or patient choice drives these results. 43 , 50 Paradoxically, we found extensive differences in selective contracting between providers and over time, without any distinguishable effect on provider budgets. Potential explanations include selective contracting having limited impact on patient flows, 51 with insurers required to (partially) reimburse noncontracted care, 17 hospitals levering market power to compensate reductions in income, 52 hospitals shifting costs between insurers as a response to selective contracting, 53 or insurers using selective contracting to concentrate care symmetrically between providers without affecting total expenditures.…”
Section: Discussionmentioning
confidence: 99%